- Thread starter
- #1

1)P one place operation

............................................m is a constant...........................

2)K one place operation

let :

1) G two place predicate

2) H two place predicate

Let :

The following axioms or assumptions)

1)for all A { H(A,m)v H(m,A)v G(A,m)}

2)for all A { H(A,m)=> G[P(A),A]}

3)for all A {H(m,A) => G[P(A),K(A)]}

4)for all A {G[K(A),m] => G(A,m)}.

5)for all A,B,C { [G(A,B) and G(A,C)]=> G(B,C)}

Then formally prove :

for all A {G[P(A),m] => G(A,m)}